Keefektifan Model Pembelajaran Inkuri Terbimbing Berbantuan Video Animasi terhadap Hasil Belajar IPA Kelas V - Karima, Retmaniar; Sulianto, Joko; Sumarno, Sumarno (Universitas PGRI Semarang, 2023)
This study aims to describe the differences in science learning outcomes between students who received the guided inquiry learning model assisted by video animation and students who received the guided inquiry learning model on the concept of heat transfer. The type of research used is a quasi-experimental with Nonequivalent Control Group Design. The population of this study are all fifth grade elementary school students in Gugus Pangeran Diponegoro, Warungasem District, for the 2022/2023 academic year. The class that became the research sample was class V at SDN Sawahjoho 01 and SDN Pesaren 01. Data were collected by observation and test techniques and then tested using the Independent Sample T-Test assisted by the SPSS program with a significance level of 0.05 or 5%. The results showed that in the aspect of scientific attitude, the significance value of the t-test was 0.04 0.05 while in the knowledge aspect the significance value of the t-test was 0.005 0.05 and in the process skills aspect, the significance value of the t-test was 0.012 0.05. This means that there are significant differences in science learning outcomes in terms of scientific attitudes, knowledge, and processing skills between students who receive the guided inquiry learning model assisted by animated videos and students who receive the guided inquiry learning model. It can be concluded that the guided inquiry learning model assisted by video animation is effective for science learning outcomes.